NS5A resistance - associated substitutions in chronic hepatitis C patients with direct acting antiviral treatment failure in Turkey - Sayan, Murat; Yildirim, Figen Sarigul; Akhan, Sila; Yildirim, Arzu Altuncekic; Sirin, Goktug; Cabalak, Mehmet; Deveci, Aydin (Elsevier Sci Ltd, 2020)
Objectives: Chronic hepatitis C (CHC) is now a more curable disease with new direct acting antivirals (DAA). Although high sustained virologic response rates, failures still occur in DAA regimens. Our objective in this study was to characterize the real-life presence of clinically relevant resistance - associated substitutions (RASs) in the HCV NS5A gene in CHC patients whose DAA regimen has failed. Methods: The study enrolled 53 CHC patients who experienced failure with DAA regimen as the prospective longitudinal cohort between 2017-2019. Genotypic resistance testing was performed via the viral population sequencing method and The Geno2pheno HCV tool was used for RAS analysis. Results: The most frequent failure category was relapse (88%) followed by non-responder (12%). For a total of 36% of patients, RASs was detected in NS5A, Y93H was the most detected RAS in GT1b infected patients (89%). Conclusions: This study establishes an HCV failure registry for Turkey in which samples were combined with clinical, virologic and molecular data of adult patients whose DAA therapy failed. RASs can occur in CHC patients with DAA treatment failures. Evaluation of RAS after DAA failure is very important before retreatment is initiated to prevent virologic failure. (C) 2020 Published by Elsevier Ltd on behalf of International Society for Infectious Diseases.
Keywords: Hepatitis C; Hepatitis C virus; NS-5 protein; Treatment failure; Sequence analysis